IMPLEMENTASI MODEL VIEW CONTROLLER (MVC) PADA APLIKASI DOA HARIAN UNTUK ANAK MUSLIM BERBASIS ANDROID - Diana -; Febrianti - (Jurnal Informatika, 2017)
Prayer is a means to communicate between slave by Allah in certain circumstances. In addition, as a spirit of prayer worship or religious sari as ever accepted in those sayings by Rasulullah SAW. Today many children are not aware of any various kinds of daily prayer because of their lack of understandingabout the prayer in daily life and also the teaching of teachersand from the child's parents. Model-View-Controller (MVC) is a concept used to encapsulate the data along with processing (model)isolate it from manipulating (controller) and display (view) torepresented on a user interface. The purpose of this study iscreate design applications daily prayers for Muslim children based on Androidthat uses the MVC method. The methodology used in the studyThis is a model RAD (Rapid Application Development). From the analysis,design, testing and implementation of programs that have been carried out against Children Daily Prayer app can be inferred application runswith both fit for purpose and planning penelitian.Model View Controller can be implemented in application development andcertainly more structured program or application.Keyword: MVC, daily prayer, muslim kids, android